2014
DOI: 10.5588/ijtld.13.0684
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing tuberculosis genotype clusters along the United States–Mexico border [Short communication]

Abstract: SUMMARY We examined the growth of tuberculosis (TB) genotype clusters during 2005–2010 in the United States, categorized by country of origin and ethnicity of the index case and geographic proximity to the US–Mexico border at the time of TB diagnosis. Nationwide, 38.9% of cases subsequent to Mexico-born index cases were US-born. Among clusters following US-born Hispanic and US-born non-Hispanic index cases, respectively 29.2% and 5.3% of subsequent cluster members were Mexico-born. In border areas, the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…However, we found that a limited proportion of cases among recent entrants were likely due to recent transmission (4.2%), and an even smaller proportion (1.7%–2.2%) were likely due to transmission from a recent entrant source case. These findings are consistent with prior studies that established relatively low rates of transmission among foreign-born persons in the United States [ 33 , 34 ]. Although data on transmission was limited to 2011 (and we could not assess trends over time), the extremely small proportion of cases associated with transmission make it unlikely that a change in transmission was a major contributor to the decline.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that a limited proportion of cases among recent entrants were likely due to recent transmission (4.2%), and an even smaller proportion (1.7%–2.2%) were likely due to transmission from a recent entrant source case. These findings are consistent with prior studies that established relatively low rates of transmission among foreign-born persons in the United States [ 33 , 34 ]. Although data on transmission was limited to 2011 (and we could not assess trends over time), the extremely small proportion of cases associated with transmission make it unlikely that a change in transmission was a major contributor to the decline.…”
Section: Discussionsupporting
confidence: 93%
“…A recent analysis suggested that tuberculosis transmission commonly occurs among U.S.-born and Mexico-born persons, particularly along the United States–Mexico border (23). This phenomenon requires further study to explore the potential relationship between U.S.-born and Mexico-born cases along the border, such as transmission within families with Mexico-born adults and U.S.-born Hispanic children.…”
Section: Discussionmentioning
confidence: 99%
“…Border states were defined as those that border with Mexico (i.e., California, Texas, New Mexico, and Arizona). Border areas were defined as public use microdata areas directly bordering Mexico and have been described elsewhere (23). …”
Section: Methodsmentioning
confidence: 99%
“…It has also been successfully used for the identification of TB clusters, with meaningful results yielded [68]. Previous studies have shown that PTB is an airborne infectious disease with spatial and temporal heterogeneous distribution, and it is believed that a better understanding of the spatial epidemiology of PTB will help guide policymakers and different stakeholders to formulate effective regional prevention and control strategies [9–11].…”
Section: Introductionmentioning
confidence: 99%